Context Mathematical Problems in The Formation of The Core Competence of Engineers of Technical Specialties; 8th World Conference on Educational Sciences (WCES-2016) - Yanushchik O. V. Olga Vladimirovna; Dalinger V. A. Viktor Alekseevich; Efremova O. N. Oksana Nikolaevna; Ustyuzhanina A. K. Anna Konstantinovna (2016, 2016)
Title screen